Molecular interference of fibrin's divalent polymerization mechanism enables modulation of multiscale material properties. (May 2015) - Brown, Ashley C.; Baker, Stephen R.; Douglas, Alison M.; Keating, Mark; Alvarez-Elizondo, Martha B.; Botvinick, Elliot L.; Guthold, Martin; Barker, Thomas H.
Abstract: Protein based polymers provide an exciting and complex landscape for tunable natural biomaterials through modulation of molecular level interactions. Here we demonstrate the ability to modify protein polymer structural and mechanical properties at multiple length scales by molecular 'interference' of fibrin's native polymerization mechanism. We have previously reported that engagement of fibrin's polymerization ' hole b ', also known as 'b-pockets', through PEGylated complementary ' knob B ' mimics can increase fibrin network porosity but also, somewhat paradoxically, increase network stiffness. Here, we explore the possible mechanistic underpinning of this phenomenon through characterization of the effects of knob B -fibrin interaction at multiple length scales from molecular to bulk polymer. Despite its weak monovalent binding affinity for fibrin, addition of both knob B and PEGylated knob B at concentrations near the binding coefficient, Kd, increased fibrin network porosity, consistent with the reported role of knob B-hole b interactions in promoting lateral growth of fibrin fibers. Addition of PEGylated knob B decreases the extensibility of single fibrin fibers at concentrations near its Kd but increases extensibility of fibers at concentrations above its Kd . The data suggest this bimodal behavior is due to the individual contributions knob B, which decreases fiber extensibility, and PEG, which increase fiber extensibility. Taken together with laser trap-based microrheological and bulk rheological analyses of fibrin polymers, our data strongly suggests that hole b engagement increases in single fiber stiffness that translates to higher storage moduli of fibrin polymers despite their increased porosity. These data point to possible strategies for tuning fibrin polymer mechanical properties through modulation of single fiber mechanics.